Single-leg cycling to maintain and improve function in healthy and clinical populations - Heidorn, C. Eric; Elmer, Steven J.; Wehmanen, Kyle W.; Martin, James C.; McDaniel, John (Frontiers in Physiology, 2023)
Exercise with reduced muscle mass facilitates greater muscle-specific adaptations than training with larger muscle mass. The smaller active muscle mass can demand a greater portion of cardiac output which allows muscle(s) to perform greater work and subsequently elicit robust physiological adaptations that improve health and fitness. One reduced active muscle mass exercise that can promote greater positive physiological adaptations is single-leg cycling (SLC). Specifically, SLC confines the cycling exercise to a smaller muscle mass resulting in greater limb specific blood flow (i.e., blood flow is no longer ‘shared’ by both legs) which allows the individual to exercise at a greater limb specific intensity or for a longer duration. Numerous reports describing the use of SLC have established cardiovascular and/or metabolic benefits of this exercise modality for healthy adults, athletes, and individuals living with chronic diseases. SLC has served as a valuable research tool for understanding central and peripheral factors to phenomena such as oxygen uptake and exercise tolerance (i.e., V̇O2peak and V̇O2 slow component). Together, these examples highlight the breadth of applications of SLC to promote, maintain, and study health. Accordingly, the purpose of this review was to describe: 1) acute physiological responses to SLC, 2) long-term adaptations to SLC in populations ranging from endurance athletes to middle aged adults, to individuals living with chronic disease (COPD, heart failure, organ transplant), and 3) various methods utilized to safely perform SLC. A discussion is also included on clinical application and exercise prescription of SLC for the maintenance and/or improvement of health.